Penerapan Budaya Perusahaan Selama Pandemi COVID-19 The Implementation of Corporate Culture During the COVID-19 Pandemic - Muhammad Athilla Ghifary; Farhan Gani; Mohamad Zein Saleh (GLOBAL SCIENTS PUBLISHER, 2025)
The COVID-19 pandemic has brought significant changes to various aspects of life, including the workplace environment and the implementation of corporate culture. The main issue examined in this study is how companies are able to maintain and adapt their organizational culture amidst a global crisis marked by uncertainty. This research aims to describe the implementation of corporate culture during the pandemic, identify the adaptation strategies employed, and analyze their impact on employee performance and engagement. The method used involves literature review and analysis of findings from previous studies, both from global and local (Indonesian) contexts. The results indicate that companies implementing strategies such as digitalized communication, empathetic leadership, and the reinforcement of core values virtually were able to maintain their organizational culture effectively. These efforts had a positive impact on employee morale, emotional engagement, and the stability of organizational performance despite the crisis situation.